Modelling Particle Capture Efficiency with Lattice Boltzmann Method (Communications in Computational Physics, 2020)
The transport and deposition of particles over a fixed obstacle set in a fluidflow is investigated numerically. A two-dimensional model, based on lattice Boltzmann(LB) method and discrete element (DE) method, is used to simulate particledeposition. The corresponding method is two-way coupling in the sense that particlemotion affects the fluid flow and reciprocally. The particle capture efficiency, as afunction of particle size and Stokes number, is investigated using one-way (effect ofthe particle on the fluid is not considered) and two-way coupling respectively. The numericalsimulations presented in this work are useful to understand the transport anddeposition of particles and to predict the single fiber collection efficiency. The effect ofobstruction shape on single fiber collection efficiency is investigated with LB-DE methods.Results show that the influence of particle on the flow field cannot be neglectedfor particles with large size. Numerical results for circular fiber collection efficiencyare in good agreement with theoretical prediction and existing correlations. Enhancedcollection efficiency is achieved by changing the fiber shape.